ANALISIS MUTU AIR MINUM ISI ULANG DI KECAMATAN KUTA SELATAN, KABUPATEN BADUNG, BALI - Putra, I Dewa Gede Natih Kacu; Nocianitri, K.A; Wipradnyadewi, Putu Ari Sandhi (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2013)
The aim of the study is to determine the quality of refill drinking water in district of Kuta Selatan, Badung regency, Bali which includes smell, taste, color, pH, turbidity, hardness, amount of dissolved solids, contamination of Coliform and Salmonella. The data obtained are presented descriptively in the form of table and compared to SNI standard quality of drinking water. The determination depot sampling of drinking water refill is done by simple random sampling method. Population depot refill drinking water amount to 22 depots and 10 depots were taken as samples by lottery and analyzed in the laboratory. The results showed refill drinking water in the District of South Kuta not meet drinking water quality standards and there are 8 depot refill drinking water that is not safe for the health of depot A and B were contaminated by Salmonella, whereas, depot D, F, G, H, I and J were contaminated by Coliform and Salmonella.
Keywords: refill drinking water, standard quality of drinking water, District of South Kuta